2021
DOI: 10.1186/s41610-020-00177-4
|View full text |Cite
|
Sign up to set email alerts
|

Cushion plant Silene acaulis is a pioneer species at abandoned coal piles in the High Arctic, Svalbard

Abstract: Background Abandoned coal piles after the closure of mines have a potential negative influence on the environment, such as soil acidification and heavy metal contamination. Therefore, revegetation by efficient species is required. For this, we wanted to identify the role of Silene acaulis in the succession of coal piles as a pioneer and a nurse plant. S. acaulis is a well-studied cushion plant living in the Arctic and alpine environments in the northern hemisphere. It has a highly compact cushi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…According to Castro et al (2002), the nursing effect on the lower soil-temperature and higher soil-moisture provided by plant cover (patch area) was clearly presented inside and at the edge of Salvia lavandulifolia as a nurse plant. In addition, the height of Silene in this study was rather low compared to the 2-8 cm height described by Oh and Lee (2021).…”
Section: Two Arctic-plants Buffer Soil-temperature Fluctuationscontrasting
confidence: 70%
See 1 more Smart Citation
“…According to Castro et al (2002), the nursing effect on the lower soil-temperature and higher soil-moisture provided by plant cover (patch area) was clearly presented inside and at the edge of Salvia lavandulifolia as a nurse plant. In addition, the height of Silene in this study was rather low compared to the 2-8 cm height described by Oh and Lee (2021).…”
Section: Two Arctic-plants Buffer Soil-temperature Fluctuationscontrasting
confidence: 70%
“…Grau et al (2014) showed that patches of Dryas octopetala × intermedia have a distinct negative effect on small-scale plant richness. Silene acaulis in Ny-Ålesund showed all interactions (positive, negative, and neutral effects on species richness) according to the different aspects (Oh and Lee 2021). Therefore, to fully understand species co-occurrence, focusing on either facilitation or competition independently may be inadequate (Losapio et al 2021).…”
Section: Plant-species Co-occurrence Pattern and Richnessmentioning
confidence: 99%